Transforming drug development: where the pharmaceutical big guns are with AI / June Choon Wai Yee - Choon, June Wai Yee (Faculty of Pharmacy, 2024)
The pharmaceutical industry has witnessed a rapid acceleration in the integration of artificial intelligence (AI) technologies over the past decade. This growing interest promises profound impacts, not only benefiting healthcare providers and patients dealing with challenging conditions but also significantly influencing the biotech sector.